Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Produk Fashion di Tiktokshop (Studi Kasus Pada Gen Z di Palembang) - Alyani, Niki (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In a case study on students in Palembang, this study aims to analyze the effect of product quality and price on purchasing decisions for fashion products at Tiktokshop. Data was gathered by means of surveys that were distributed to Gen Z residents of Palembang. Multiple linear regression was used to analyze the data in order to determine the extent to which the price and product quality variables influence purchasing decisions. This study involved 52 respondents. Based on the study, it can be seen that: (1) The influence of price does not have a significant impact on purchasing decisions; (2) Product quality has a significant positive impact on purchasing decisions.